Traditional Versus Velocity-Based Resistance Training in Competitive Female Cyclists: A Randomized Controlled Trial - Montalvo-Pérez, Almudena; Alejo, Lidia B.; Valenzuela, Pedro L.; Gil-Cabrera, Jaime; Talavera, Eduardo; Lucia, Alejandro; Barranco-Gil, David (Frontiers in Physiology, 2021)
The aim of the study was to assess the effects of a short-term velocity-based resistance training (VBRT, where exercise intensity is individualized based on the loads and repetitions that maximize power output) program compared with traditional resistance training (TRT, where the same number of repetitions and relative load are used for everyone) to improve body composition, strength and endurance performance in competitive female cyclists. 17 participants were randomly assigned to 6 weeks (2 sessions·week-1) of TRT (n=8) or VBRT (n=9), during which they maintained their normal endurance program. Both interventions included the squat, hip thrust and split squat exercises. Training loads were continuously registered, and outcomes included measures of muscle strength/power, body composition, and endurance performance (including an incremental test and an 8-minute time trial). No between-group differences were found for overall training loads during RT or cycling sessions (p>0.05). Both interventions led to significant improvements in all strength/power-related parameters, but VBRT induced greater improvements for maximum strength and power as assessed with the hip thrust exercise (p<0.05). Significant increases in muscle mass were observed with VBRT (p<0.05) but not TRT. Both interventions led to significant improvements in the power output during the time trial, with no differences between groups. The addition of a short-term intervention of either VBRT or TRT to the usual endurance training program of competitive female cyclists results in improved time trial performance, but the former might induce superior gains on body composition and strength.